Application of Data Mining Using the K-Medoids Algorithm for Poverty Index Clustering - Muhammad Faisal; Wiranti Sri Utami (CCIT Journal, 2022)
Poverty index is a term for measuring poverty, this is done by a government agency or commonly referred to as the Central Statistics Agency (BPS). The poverty index or poverty rate is the percentage of the population in a province who is below the poverty line, which is the minimum in obtaining an adequate standard of living. In the government's efforts to reduce the level of poverty in a province, the government often provides special assistance programs for people belonging to the poverty line. Based on the explanations that have been discussed, a conclusion can be drawn. This research can be done using the Data Mining technique to group the total Poverty Index by Province in Indonesia using the K-Medoids Algorithm, then by determining the Clusters randomly. The results of this study are expected to assist the government in providing assistance to the affected population below the poverty line.